RÁDIO, TECNOLOGIA E SOCIEDADE: O desenvolvimento da Radiodifusão Digital no Brasil - Archangelo, Flávio Aurélio Braggion (2008)
The thesis works with the broadcasting technology in process of digitalization. Select the historical and fundamental marks that contribute to build one communication industry structure, characteristics demonstrated in debates and arguments around the digitalization of the sector. Through the description of the digital technologies to be used in that transition, it was able to identify the technological potentials that are social shaped in the acts of standardization of the technique, showing the limitations and the conservative face that one new technology could represent.(AU)